GABA(B) receptor-mediated ERK1/2 phosphorylation via a direct interaction with Ca(v)1.3 channels - Im, Bo-Hye; Rhim, Hyewhon (ELSEVIER IRELAND LTD, 2012)
Neuronal L-type Ca2+ channels play pivotal roles in regulating gene expression, cell survival, and synaptic plasticity. The Ca(v)1.2 and Ca(v)1.3 channels are 2 main subtypes of neuronal L-type Ca2+ channels. However, the specific roles of Ca(v)1.2 and Ca(v)1.3 in L-type Ca2+ channel-mediated neuronal responses and their cellular mechanisms are poorly elucidated. On the basis of our previous study demonstrating a physical interaction between the Ca(v)1.3 channel and GABA(B) receptor (GABA(B)R), we further examined the involvement of Ca(v)1.2 and Ca(v)1.3 in the GABA(B)R-mediated activation of ERK1/2, a kinase involved in both CREB activation and synaptic plasticity. After confirming the involvement of L-type Ca2+ channels in baclofen-induced ERK1/2 phosphorylation, we examined a specific role of Ca(v)1.2 and Ca(v)1.3 channels in the baclofen effect. Using siRNA-mediated silencing of Ca(v)1.2 or Ca(v)1.3 messenger, we determined the relevance of each channel subtype to baclofen-induced ERK1/2 phosphorylation in a mouse hippocampal cell line (HT-22) and primary cultured rat neurons. In the detailed characterization of each subtype using HEK293 cells transfected with Ca(v)1.2 or Ca(v)1.3, we found that GABA(B)R can increase ERK1/2 phosphorylation and Ca(v)1.3 channel activity through direct interaction with Ca(v)1.3 channels. These results suggest a functional interaction between Ca(v)1.3 and GABA(B)R and important implications of Ca(v)1.3/GABA(B)R clusters for translating synaptic activity into gene expression alterations. (c) 2012 Elsevier Ireland Ltd. All rights reserved.
Keywords: FACILITATE L-TYPE; CALCIUM-CHANNELS; CA2+ CHANNEL; HIPPOCAMPAL-NEURONS; ACTIVATION; ALPHA(1G); SUBUNITS; NUCLEUS; PATHWAY; BRAIN